2017
DOI: 10.1007/s00335-017-9683-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, classification, and functional analysis of the basic helix–loop–helix transcription factors in the cattle, Bos Taurus

Abstract: The basic helix-loop-helix (bHLH) transcription factors (TFs) form a huge superfamily and play crucial roles in many essential developmental, genetic, and physiological-biochemical processes of eukaryotes. In total, 109 putative bHLH TFs were identified and categorized successfully in the genomic databases of cattle, Bos Taurus, after removing redundant sequences and merging genetic isoforms. Through phylogenetic analyses, 105 proteins among these bHLH TFs were classified into 44 families with 46, 25, 14, 3, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…Gene analysis based on interaction between genes can effectively produce biological information, providing valid scientific reference for the diagnosis, treatment and improvement of prognosis. Following the rapid development of genomic science, a large quantity of genomic data and gene expression data have provided a novel basis for the investigation of gene-gene and gene-environment interactions (23)(24)(25). By analyzing the existing data through systems biology approaches, it is possible to investigate the association between gene function, protein interaction and the occurrence of diseases, and construct a detailed network of the occurrence and progression of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Gene analysis based on interaction between genes can effectively produce biological information, providing valid scientific reference for the diagnosis, treatment and improvement of prognosis. Following the rapid development of genomic science, a large quantity of genomic data and gene expression data have provided a novel basis for the investigation of gene-gene and gene-environment interactions (23)(24)(25). By analyzing the existing data through systems biology approaches, it is possible to investigate the association between gene function, protein interaction and the occurrence of diseases, and construct a detailed network of the occurrence and progression of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TCF4 was identified as an indispensable mediator in the inhibitory effect of tumor necrosis factor α (TNFα) on adipogenesis (Cawthorn et al, 2007), suggesting that TCF4 is pro-fibrogenic and is important for the fibrogenic fate determination of FAPs. The expression of TCF4 in cattle has not been extensively studied possibly due to the presence of large number of TCF4 transcription isoforms in cattle (Li and Liu, 2017). However, a study reported a possible single nucleotide polymorphism (SNP) effect of TCF4 on the lean mass of beef cattle (Zhang et al, 2018), which might be related to the reported role of TCF4 + fibroblasts in skeletal muscle development and growth (Mathew et al, 2011;Murphy et al, 2011).…”
Section: Transcription Factor 4 (Tcf4)mentioning
confidence: 99%
“…bHLH family members contain two highly conserved and different functional domains, namely, the basic region and the helix-loop-helix (HLH) region, with a total of approximately 50-60 amino acids [7]. The basic region consists of approximately 15 amino acids, is located at the N-terminus of the domain, and can recognize and bind the E-box and G-box.…”
Section: Introductionmentioning
confidence: 99%